Brand Positioning as A Mediator in The Relationship Between Social Media Quality and Brand Loyalty: An Applied Study on The Private Universities in Egypt - Mussa, Mona H. (The Arab Journal of Administration, 2025)
The research investigates the role of brand positioning as a mediator in the relationship between social media quality and brand loyalty in private higher education institutions in Egypt from the student’s perspective. The quantitative method was the research method. The primary data was collected by the online questionnaire from the students enrolled in private universities in Egypt. Convenience sampling was used. The sample size was 400. A total of 384 responses were collected and valid. The data were analyzed via (SPSS v22). The findings indicated that there is a significant relationship between social media quality and brand loyalty, and brand positioning mediates this relationship. Additionally, the model has a high ability to predict brand loyalty through social media quality and brand positioning. The study recommends private universities to depend on social media as a strategic marketing communication tool to build brand positioning and brand loyalty. The research is limited to private universities in Egypt, and findings may apply to other institutions.